R graphs cookbook : detailed hands-on recipes for creating the most useful types of graphs in R-starting from the simplest versions to more advanced applications /: detailed hands-on recipes for creating the most useful types of graphs in R-starting from the simplest versions to more advanced applications. (©2011) - Unknown
No abstract available